Financial Distress pada PT Panasia Indo Resources Tbk - Akhbar Nugraha; Catur Martian Fajar (Jurnal Inspirasi Bisnis dan Manajemen, 2018)
Abstract. Bankruptcy in the company is characterized by a continuous decline in financial performance. The purpose of this study is to assess the influence of current ratio, debt to assets ratio, working capital turnover and net profit margin of the company on financial distress at PT Panasia Indo Resources Tbk. used is the explanatory survey. The result of the research shows that the existence of negative and insignificant influence of current ratio in predicting financial distress, debt to asset ratio has positive and insignificant influence in predicting Financial distress, working capital turnover has negative and insignificant influence in predicting Financial distress and net profit margin has a negative and significant influence in predicting Financial distress. Simultaneously, the current ratio, debt to assets ratio, working capital turnover and net profit margin jointly have a significant effect on the condition of Financial distress at PT Panasia Indo Resources Tbk. Keywords: Current ratio; Debt to assets ratio; Working capital turnover; Net profit margin; Financial distress Abstrak. Kebangkrutan diperusahaan ditandai dengan adanya penurunan kinerja keuangan yang terjadi terus-menerus. Tujuan penelitian ini adalah untuk mengkaji pengaruh current ratio, debt to assets ratio, working capital turnover dan net profit margin perusahaan pada financial distress pada PT Panasia Indo Resources Tbk. Metode penelitian yang digunakan adalah explanatory survey. Hasil penelitian menunjukkan bahwa adanya pengaruh negatif dan tidak signifikan current ratio dalam memprediksi financial distress, debt to assets ratio mempunyai pengaruh positif dan tidak signifikan dalam memprediksi Financial distress, working capital turnover mempunyai pengaruh negatif dan tidak signifikan dalam memprediksi Financial distress dan net profit margin mempunyai pengaruh negatif dan signifikan dalam memprediksi Financial distress. Secara simultan current ratio, debt to assets ratio, working capital turnover dan net profit margin secara bersama-sama berpengaruh signifikan terhadap kondisi Financial distress pada PT Panasia Indo Resources Tbk. Katakunci: Current ratio; Debt to assets ratio; Working capital turnover;  Net profit margin; Financial distress